A Comparative Study of the Morals of PAI IAIN Kerinci Students Who Participate in the Ma'had Al-Jamiah Program with Non-Participants - Yuli Amanah; Noperta Noperta; Albertos Damni (PALAPA, 2024)
This research was conducted to determine the difference in moral levels between Islamic Education (PAI) students who participated in the Ma'had al-Jamiah program at IAIN Kerinci and those who did not participate (non-participants). The method used was a quantitative research method with a survey approach. The questionnaire consisted of 10 items containing indicators of morality towards Allah SWT, morality towards fellow human beings, and morality towards the environment. The total sample size was 70 PAI students, comprising 35 students who participated in the Ma'had al-Jamiah program and 35 non-participants. This study conducted normality tests and statistical tests using SPSS. Based on the normality test, the morality of PAI students who participated in the program was normally distributed (significance value 0.071 > 0.05), while PAI students who did not participate in the program were not normally distributed (significance value 0.00 < 0.05). Therefore, data analysis was conducted using parametric statistical tests with Mann Whitney U. The results of the statistical tests showed that the significance value for morality (0.682) was greater than 0.05. Thus, it can be concluded that there is no significant difference between PAI students who participated in the Ma'had al-Jamiah program at IAIN Kerinci and PAI students who did not participate in the program. However, based on the interval questionnaire scores, the moral level of PAI students who participated in the program was categorized as Good (3.07), while students who did not participate were categorized as Fairly Good (2.82). Therefore, it can be said that both groups of PAI students have good moral levels.